Mid-term outcomes of atrioventricular valve repair in functional single ventricle patients - Jin, Yong-Qiang; Wu, Qing-Yu; Zhang, Xiao-Ya; Fan, Li-Xin; Zhang, En-Rui; Xue, Hui; Zhang, Ming-Kui (Frontiers in Cardiovascular Medicine, 2024)
BackgroundSurgical treatment of functional single ventricle combined with atrioventricular valve regurgitation remains a clinical challenge. The outcomes of atrioventricular valve repair in patients with single ventricle are limited.MethodsA retrospective study was conducted of all 28 patients with functional single ventricle treated with single-ventricle palliation who underwent atrioventricular valve operation at the First Hospital of Tsinghua University between April 2007 and October 2022.ResultsIn our cohort, the female/male ratio was 7:21, with an average age of 8.7 ± 6.0 (0.75–26) years. Half of patients (50%) were right-ventricle type for single-ventricle morphology. 18 patients (64.3%) were with a common atrioventricular valve. Twenty-three patients (82.1%) were combined with heterotaxy syndrome. Pre-operatively, twenty-four patients (85.7%) were diagnosed with severe atrioventricular valve regurgitation. AVV was repaired at the Glenn (n = 16, 57.1%), Glenn-Fontan (n = 2, 7.1%) and Fontan (n = 10, 35.7%) stage, respectively. Valve plastic techniques included valve annulus/commissure constriction (n = 24), clefts repair (9 cases), edge-to-edge suturing (13 cases) and common atrioventricular valve separation (4 cases). The early mortality was 3.6% (1/28). All survival patients were observed with improved regurgitation situations. Twenty-two patients (78.5%) were observed with no more than mild regurgitation postoperatively. The mean follow-up time was 5.4 ± 2.9 years (range, 3.08–11.83 years), with late mortality of 11.1% (3/27). All these three cases were observed with a severe regurgitation by echocardiogram in the last follow-up. Besides, reoperation rate of this cohort was 3.6% (1/28).ConclusionsAVV repair could significantly improve AVV function in SV patients combined with severe AVVR, with satisfactory mid-term results. Part of the cohort showed poor prognosis due to repeated AVVR. Regular follow-up by echocardiogram is critically important for these patients.